2020
DOI: 10.1021/acsabm.0c00555
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Tartaric Acid Improves Fracture Toughness of Bioactive Brushite–Collagen Bone Cements

Abstract: Brushite cements are promising bone regeneration materials with limited biological and mechanical properties. Here, we engineer a mechanically improved brushite–collagen type I cement with enhanced biological properties by use of chiral chemistry; d - and l -tartaric acid were used to limit crystal growth and increase the mechanical properties of brushite–collagen cements. The impact of the chiral molecules on the cements was examined with Fourier-transform infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
(158 reference statements)
0
2
0
Order By: Relevance
“…(R, R)-tartaric acid is an organic acid involved in glyoxylate and dicarboxylate metabolism (KEGG PATHWAY: map00630), which links to ascorbate and aldarate metabolism (KEGG PATHWAY: map00053). Recent studies reported the effect of L-tartaric acid on the improvement bone cement mechanical toughness [55], pointing to a possible usefulness for bone applications.…”
Section: Role Of Osteogenic Medium Componentsmentioning
confidence: 99%
“…(R, R)-tartaric acid is an organic acid involved in glyoxylate and dicarboxylate metabolism (KEGG PATHWAY: map00630), which links to ascorbate and aldarate metabolism (KEGG PATHWAY: map00053). Recent studies reported the effect of L-tartaric acid on the improvement bone cement mechanical toughness [55], pointing to a possible usefulness for bone applications.…”
Section: Role Of Osteogenic Medium Componentsmentioning
confidence: 99%
“…Template-driven biomineralization regulated by the extracellular matrix to obtain highly integrated composites scaffolds has attracted great attention during the past two decades. 38,49 So far, there are several biomineralization strategies to incorporate CaP into biopolymer-based 50–52 or synthetic polymers-based 53–56 scaffolds, such as incubation with simulated body fluid (SBF), 57,58 in situ precipitation 48,59,60 or template-driven mineralization. 61 Urea-mediated solution mineralization is a high-efficiency approach for preparing mineralized scaffolds; however, it starts at low pH (2–3) and ends at high temperature (about 80 °C) 39 so this method cannot be applied to the PLGA/PSBMA scaffolds because PLGA is an acid-triggered hydrolysable material with a glass transition temperature of around 32 °C.…”
Section: Resultsmentioning
confidence: 99%